Splintering Urbanism : networked infrastructure, technological mobilities and the urban condition - Graham, Stephen; Marvin, Simon (Oxon: Routledge, 2006)
Splintering Urbanism makes an international and interdisciplinary analysis of the complex interactions between infrastructure networks and urban spaces.
Understanding splintering urbanism -- Exploring the splintering metropolis -- Placing splintering urbanism --
Keywords: PL